Enhancing biohydrogen production from lignocellulosic biomass of Paulownia waste by charge facilitation in Zn doped SnO2 nanocatalysts. (July 2022) - Tahir, Nadeem; Nadeem, Faiqa; Jabeen, Farzana; Rani Singhania, Reeta; Yaqub Qazi, Umair; Kumar Patel, Anil; Javaid, Rahat; Zhang, Quanguo
Graphical abstract: Highlights: Zn doping leads to the generation of charge carriers through charge compensation. Excess charges help to regulate H2 production by increasing charge transferring. Excess charges increase total hydrogen yield by ∼ 47%. The decrease in VFAs with Zn doping shows an increase in bacterial metabolism. Zn doping helps to reduce the lag time and required catalyst concentration. Abstract: The goal of this research was to study the role of excess charges in regulating biohydrogen production from Paulownia . The excess charges were generated through charge compensation in SnO2 nanocatalysts by Zn doping. The maximum hydrogen yield of 335 mL was observed at 8%Zn doping with a concentration of 150 mg/L, 47% higher as compared to standard sample. It was observed that the hydrogen production rate increased with Zn doping and the highest value (77 mL/h) was observed for 8%Zn at 24 h. The decrease in the total amount of byproducts (2.52 g/L from 4.28 g/L) at 8% Zn indicates an increase in bacterial metabolism. The lowest value of oxidation–reduction potential (-525 mV) at 24 h for 8%Zn confirms that Zn doping provides excessive electrons to the fermentative medium which helps the bacteria to transfer electrons faster during the redox reaction, hence, enhancing the enzymatic process and eventually hydrogen production.